Rothia mucilaginosa Meningitis in a Child with Myelodysplastic Syndromes - Fumihiro Ochi; Ryota Nakamura; Reiji Miyawaki; Kyoko Moritani; Shinobu Murakami; Hisamichi Tauchi (Case Reports in Pediatrics)
Rothia mucilaginosa is a Gram-positive coccus and an opportunistic pathogen in immunocompromised hosts. The microorganism has been implicated in serious infections, including bacteremia meningitis or endocarditis. However, there is a dearth of investigations on meningitis, especially in children. As this infection is rare and only a few cases have been recorded, evidence-based guidelines for adequate infection treatment are lacking. We herein report the case of a 12-year-old boy with myelodysplastic syndromes (MDS) presenting with a change in mental status who was diagnosed as having febrile neutropenia and bacterial meningitis caused by R. mucilaginosa at 23 days after unrelated cord blood transplant. In our case, the minimum inhibitory concentrations (MICs) of meropenem and vancomycin (VCM) were both ≤1 μg/mL, whereas the MIC of daptomycin (DAP) was 4 μg/mL. The patient was treated with intravenous antimicrobial therapy due to meropenem for 43 days because he had febrile neutropenia. During follow-up, the patient had no neurological complications. We retrospectively reviewed the antimicrobial susceptibility of all R. mucilaginosa isolates (n = 5) from blood or cerebrospinal fluid cultures at our hospital. The MIC of VCM was <0.5 μg/mL for all strains, whereas the MIC of DAP was ≥2 μg/mL for all strains. The MIC of MEPM was >1 μg/mL for one strain. We recommend choosing VCM as the primary treatment for invasive R. mucilaginosa infections until antimicrobial susceptibility results are known, especially in immunocompromised children.